The genus Bipinnula (Orchidaceae: Chloraeinae) in Argentina - Sanguinetti, Agustin (2015)
A taxonomic synopsis of Bipinnula Comm. ex Juss. (Orchidaceae: Chloraeinae) in Argentina is presented. Three species are recognized: B. biplumata Rchb.f., B. penicillata (Rchb.f.) Cisternas & Salazar and B. polysyka Kraenzl. A key to separate these species is presented and their distribution in Argentina is presented. All species are described in detail and photographs of diagnostic vegetative and floral features, as well as distributional, ecological and nomenclatural comments are included. Lectotypes for the basionyms Arethusa biplumata L.f., Chloraea arechavaletae Kraenzl. and B. polysyka Kraenzl. are designated. All studied species are terrestrial orchids that grow in grasslands of the heavily transformed Pampas biome; two of them are restricted to a few counties. Therefore, an assessment on their conservation status is urgently needed.